The Influence of Motivation, Competence, and Discipline on Employee Performance (Study at Baleendah District Bandung Regency Government) - Harto, Agung Puji Duwi; Siddiq, Andhika Mochamad (Jurnal Bisnis, Manajemen, dan Ekonomi, 2025)
This study aims to evaluate the influence of motivation, competence, and work discipline on employee performance at the Baleendah District Office, Bandung Regency. The study employed a quantitative approach using descriptive and verification methods. The entire population, totaling 80 employees, both civil servants (ASN) and non-ASN, was sampled using a census method. Primary data was obtained through a closed-ended questionnaire and analyzed using multiple linear regression techniques. The results indicate that all variables are in the very high descriptive category. Partially, competence and work discipline have a positive and significant influence on employee performance, while motivation has a positive but insignificant influence. Simultaneously, all three variables contribute significantly to improved performance. The coefficient of determination (R²) of 68.2% indicates that the model has strong ability to explain variations in employee performance. These findings have important implications for public sector human resource management, particularly in designing training programs and fostering work discipline based on active employee participation